Analisis dampak kanvas bisnis model pada proyek kewirausahaan sosial untuk aplikasi keselamatan diri - Benedicta Evienia Prabawanti (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2022)
The beginning of the COVID-19 pandemic required humans to spend more time at home because of the government's policy of limiting activities. This study turned out to be a source of trigger for the emergence of social violence in society. Data shows that the level of violence in Indonesia, particularly in Jakarta, is increasing as the Covid-19 pandemic continues. All forms of violence can occur anywhere and anytime. Although various services are provided to victims of violence and improvements in education and technology this is not enough to reduce the violence in Indonesia. This article was written using a qualitative method by analyzing the social impact of the business model canvas to design a feel safe application (FSA). The data used helps strengthen why this FSA project needs to be made as a social entrepreneurship project. The data was obtained through secondary data from government publications and publications related to research that discussed increased social violence in the household and the environment since the COVID-19 pandemic. Implementing FSA as one of the social entrepreneurship projects is expected to impact the community by minimizing the number of violence and increasing public awareness of violence and its impact on victims.